Six Academic Attitudes of Muslim Scholars Toward Knowledge Sources in the Digital Era - Fardu Hasan; Tomikal Tomikal; Mustamin Gilling (Muaddib: Journal of Islamic Teaching and Learning, 2025)
In the early period of Islam, knowledge sources were centralized in the Quran and the Prophet Muhammad (peace be upon him). Over time, these sources expanded into diverse forms, and in the contemporary digital era, knowledge acquisition is heavily influenced by technology-based information. The challenge lies in the fact that digital sources cannot be fully trusted in the same way as the Quran and Sunnah. This article aims to analyze the appropriate attitudes of Muslim academics in filtering and utilizing knowledge sources in the digital age. A qualitative content analysis approach was employed, drawing on Quranic verses, Hadith, theoretical frameworks, expert opinions, and peer-reviewed articles indexed globally. Data were thematically analyzed using Nvivo 12 with Miles and Huberman’s interactive technique. The findings reveal six essential attitudes for Muslim academics: i) critical and selective thinking, ii) adherence to Islamic ethics, iii) effective use of technology as a medium of knowledge, iv) preservation of academic integrity, v) wise management of time and information consumption, and vi) orientation toward the advancement of the ummah. These attitudes serve as a reference framework and ethical guideline for Muslim academics to intelligently filter digital information. The study contributes to the discourse on Islamic academic ethics in the digital era and provides a foundation for future research in broader contexts.